2020
DOI: 10.1039/c9ra08654d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of green-emitting carbon quantum dots with double carbon sources and their application as a fluorescent probe for selective detection of Cu2+ ions

Abstract: Green-emitting carbon quantum dots (G-CQDs) were prepared using tartaric acid and bran by one-pot solvothermal treatment and had photoluminescence quantum yields (PL QY) as high as 46%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Although FB 1 has an effect on the catalytic effect of DTSA CDs, it cannot be said that only FB 1 has an effect on it, and it has been reported that some metal ions 27 and organic matter 28 also have an effect on CDs. Therefore, F10 needs to be added to ensure specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Although FB 1 has an effect on the catalytic effect of DTSA CDs, it cannot be said that only FB 1 has an effect on it, and it has been reported that some metal ions 27 and organic matter 28 also have an effect on CDs. Therefore, F10 needs to be added to ensure specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the low cost, biocompatibilty, and distinct PL properties proves these C-dots could potentially be produced on an industrial scale as a new fluorescent ink for versatile applications [49]. Xu et al used tartaric acid and bran as starting precursors to synthesize green light-emitting CDs [50]. The one-pot solvothermal process produces CDs with 46% PLQY.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots can be made in a variety of ways, including hydrothermal, [10][11][12][13][14] solvothermal, [15][16][17] electrochemical, [18][19][20] arc discharge, laser ablation, 2,21 pyrolysis, and others. [22][23][24][25] However, to improve water solubility and fluorescence, 2 these synthetic approaches require multiple stages, including pricey precursors, post-preparative treatment, and a surface passivating agent. One-step self-passivated carbon dot preparations have recently piqued interest, however they are time-consuming, expensive, and need a high temperature, as well as a poor quantum yield (QY) and limited solubility.…”
Section: Introductionmentioning
confidence: 99%